Surface exposure dating of moraines in the Chagan Uzun Valley, Altai Mountains - Garcia Morabito, Ezequiel (2016)
The mountains in southern Siberia (Altai, Sayan, Transbaikalia) wereglaciated repeatedly during the Quaternary, and the glacial sedimentsand landforms there are valuable archives for paleoenvironmental and climate reconstructions. However, studies focusing on glacialchronologies in these mountain ranges are still very scarce, and theextent and timing of glacier advances remains poorly constrained(e.g., Lehmkuhl et al. 2011; Agatova et al. 2014). We have used cosmogenic 10Be surface exposure dating toestablish a glacial chronology for the Chagan Uzun Valley in thesouthern Chuja Range in the Russian Altai. We targeted six morainecomplexes and sampled gneiss boulders and quartz cobbles. Exposureages vary widely on the individual moraines, making interpretationsin terms of depositions ages and timing of glacial advancesdifficult. Assuming negligible nuclide inheritance and interpretingthe oldest sample from a moraine as best available estimate, massiveglaciation occurred as early as ~84 ka. Subsequent, successively lessextensive glacial advances probably occurred at >40 ka (MIS4?),and 21-24 ka. Ourdata highlight the difficulty to apply surface exposure dating ofglacial landforms in cold, continental regions, most likely due tolong-lasting landform surface instability. Our results neverthelessadd additional evidence for an early local LGM in Siberia,significantly predating the global LGM.